Synthesis of Bio-Silver Nanoparticles using Leaf Extract of Cymbopogon nardus and Examination of Their Physical and Anti-Bacterial Properties - Patty, Philipus J; Wattimena, Synodalia C; Silahooy, Veince B (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2025)
In this study, antibacterial activities of bio-silver nanoparticles synthesized using leaf extract of Cymbopogon nardus against Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Escherichia coli (E. coli) were assessed. For this purpose, the disc diffusion and spectrophotometric methods were used. Before the antibacterial assessment, the physical properties of the silver nanoparticles were characterized. UV-VIS spectroscopy was used to determine the wavelength of the localized surface plasmon resonance, while FTIR was used to identify the functional group on the particles. For the shape and size distribution of the particles, TEM was used. The UV-VIS spectrum shows 435 nm as the wavelength of localized surface plasmon resonance while the FTIR spectrum indicates the presence of the extract on the surface of the particles, suggesting the action of extracts as the reducing as well as capping agents. Most of these nanoparticles observed are spherical, and their diameters vary from 7.0 nm to 31.0 nm with the mean diameter calculated to be 15.7±4.60 nm. Results from both diffusion disc and spectrophotometric methods show that the silver nanoparticles can inhibit the growth of both gram-positive (S. aureus) and gram-negative (E. coli) bacteria. In the diffusion disc method, the diameter of the inhibition zone was found to be 0,83 ± 0,03 cm for S. aureus and 0,63 ± 0,03) cm for E. coli. Statistical analysis shows no significant difference between the two. In the spectrophotometric method, the optical density of bacteria without the nanoparticles increases, while it levels off when the nanoparticles are applied. The significant difference between the two occurs 6 hours after introducing silver nanoparticles to E. coli and S. aureus. The results show that the silver nanoparticles inhibit the growth of both S. aureus and E. coli equally